Development of Mollusca Diversity E-Booklet at Bondo Beach Jepara to Improve Student Learning Outcomes - Laela Noor Fa’izah; Ning Setiati; Nana Kariada Tri Martuti (Journal of Innovative Science Education, 2023)
Observation results obtained by the availability of learning resources used are still less diverse and do not support the learning objectives achieved. The learning resources used are still limited to book packages, Student Worksheets (LKS) and Power Points (PPt). The biodiversity in Jepara Bondo Beach is very high which has not been used as a source of learning biology at SMA Islam Nusantara and SMA PGRI Jepara. The environment around the school has not been used as a learning resource because it has not represented biological wealth. Therefore, Jepara Bondo Beach is a representative place to be used as a source of learning that is close to schools. This study aims to develop an e-booklet on the diversity of Mollusca at Bondo Beach, Jepara in a factual, systematically arranged according to the material, valid, effective in increasing learning outcomes in the cognitive and psychomotor domains in practicing oral communication skills in the sub-material classification of living things. This research uses the development method (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research data were analyzed for its characteristics, validity and effectiveness. The results of the study can be concluded that the e-booklet characteristics of Mollusca paintings on Bondo Beach Jepara are factual which are arranged systematically so that they can reach TP 10.1 to 10.3, the e-booklet is very valid and feasible to use based on expert judgment, and is effective in increasing cognitive and psychomotor learning outcomes in practicing oral communication skills.